Done with a degree? Immigration-specific disparities among holders of bachelor’s degrees in the transition to graduate studies in Germany - Neumeyer, Sebastian; Pietrzyk, Irena (Frontiers in Sociology, 2023)
In many Western societies, immigrants make more ambitious educational choices than their native counterparts of equal academic achievement and social origin. These ambitious decisions have been mainly observed at early and middle educational stages, whereas research on choices within higher education is scarce. Against this background, we investigate whether immigrants make more ambitious decisions than natives do also after having graduated from bachelor’s programs in Germany. We theoretically derive that variations in immigration-specific differences in educational choices can be expected based on social origin and country of origin, as well as between the application for and the actual enrollment in graduate studies. Using survey data on educational trajectories of bachelor’s degree holders, we observe our expectations to be confirmed for the investigated sample. First, immigration-specific differences in educational choices vary by social origin and are increased for graduates from low social origins. This finding supports that immigrants strive for status maximization, an idea that we understand as a theoretical specification of the motive for status gain. Second, they vary by country of origin, which suggests cultural factors to be subordinate. Third, immigration-specific differences in applications are more pronounced than differences in actual transitions, indicating that immigrants have fewer chances of transforming their aspirations into actual transitions. We conclude by discussing these three aspects more broadly.